Demographic Consequences of Small-Scale Fisheries for Two Sex-Changing Groupers of the Tropical Eastern Pacific - Chong-Montenegro, Carolina; Kindsvater, Holly K. (Frontiers in Ecology and Evolution, 2022)
The effects of fishing on the demography and population ecology of sex-changing fishes are largely unknown, despite the fact that their fisheries provide important economic and nutritional resources in coastal communities throughout the tropics, especially in Latin America. Species with female-first sex change often have naturally skewed sex ratios in the adult population, and fishing pressure can alter this natural bias, limiting egg production and fertilization success. How fishing alters demography and population vital rates depends on which sizes and sexes are selected. We consider two types of fishery selectivity – asymptotic (selecting the largest fish) and plate-sized (selecting fish between in a narrow, but small, size range) – that to represent fisheries for two important fish species of the Tropical Eastern Pacific, the Pacific goliath grouper (Epinephelus quinquefasciatus) and the endemic sailfin grouper (Mycteroperca olfax) of the Galapagos Islands, known locally as bacalao. Each of these large, long-lived species support small scale fisheries of significant value, but there is limited information on fishing effort, selectivity, or population trends. Using a population model, we estimate how the biology of these species contributes to their risk of overexploitation under different possible scenarios of fishing and reproductive biology. Specifically, we consider how variation in growth rates and fertilization rates interact with selectivity to affect age structure and sex ratios. We compare two metrics of population status: the spawning potential ratio (SPR), and the relative standing biomass after fishing (B_F/B_0). In our modelled populations, when fertilization rates were reduced, fishing rapidly decreased the spawning potential of both species, but did not affect biomass at moderate levels of fishing mortality. However, we predict low fertilization success, fast somatic growth, and asymptotic selectivity of fisheries for sex-changing species decreases both spawning potential and biomass, even at low levels of exploitation, suggesting these factors can cause rapid depletion of sex-changing species. Our findings highlight key gaps in our knowledge of spawning behavior and fertilization success of sex-changing fishes that must be filled if we are to sustainably manage these culturally and economically significant fisheries.